Sistems With a "Flixible Bottom" of the Bilding Objekt (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The article describes the most frequently used methods for ensuring seismic resistance of buildings and structures designed for construction in seismic areas.